Conocarpus Tree – A Boon or Bane? - Ramanjaneyulu, A. V.; Chaitanya, T.; Joseph, B. (Chronicle of Bioresource Management, 2023)
Conocarpus is an evergreen tree and is projected to be the best one for green corridors or green belts in towns and cities. Of late, there is a continuous debate on it’s harmful nature such as blocking water and drainage pipelines in the habitations and certain health issues like pollen allergy, asthama etc., Further, the governments started imposing ban on future plantations. On the otherhand, the published literature reveals potential benefits to the mankind. So, the public, intelligentia, policy makers, governments etc., are under confusion regarding future course of action. Hence, it is high time to bring forth the facts and figures regarding merits and demerits of this wonderful pleasure tree.